Private property and state power : philosophical justifications, economic explanations, and the role of government - Huffman, James L.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2013)
This book details the relationship between private property and government. As private property is important to both individual welfare and the public interest, the book provides an intellectual framework for the analysis and resolution of contemporary property rights disputes.
Keywords: Science; Science; Science, general